Length-weight relationship and population genetic of two marine gastropods species (Turbinidae: Turbo sparverius and Turbo bruneus) in the Bird Seascape Papua, Indonesia (Biodiversitas Journal of Biological Diversity, 2016)
Length-weight relationship and population genetic of two marine gastropods species (Turbinidae: Turbo sparverius and Turbo bruneus) in the Bird Seascape Papua, Indonesia. Biodiversitas 17: 208-217. Turbo sparverius and Turbo bruneus are herbivorous grazers gastropod that lived on the rocky intertidal area, which have a role in maintaining algae on the intertidal ecosystem. Local people in Papua have exploited them for food and souvenirs. Even though this exploitation might affect their genetic diversity and population, a study of the genetic structure of these species has not been previously reported. This study aimed to analyze the morphometric, genetic diversity, population structure and connectivity of T. sparverius and T. bruneus in coastal water of West Papua, Indonesia. The results showed that the growth pattern of T. sparverius and T. bruneus in all populations were negative allometric, which means that weight gain was slower than length. Haplotype diversity value of all population T. sparverius and T. bruneus were 0.657-0.705 and 0.739-0.816, respectively. In addition, the haplotype diversity of eachÂ population showed a high level of diversity. The genetic structure was found in all population of T. sparverius and T. bruneus with F value-0.037-0.201 and 0.031, respectively. Population structure and phylogenetic tree showed the closeness of genetic due to gene flow between both T. sparverius and T. bruneus. Genetic distance value between populations T. sparverius and T. bruneus are very low were 0.002 and 0.003-0.004, respectively. High genetic similarity might occur due to condition and direction of current flow mediating ofÂ gene transport among population, and the similarity of habitats in each population.